PRELIMINARY STUDY ON THE USE OF IPOMOEA CARNEA POWDER AS A REINFORCEMENT MATERIAL IN THE PRODUCTION OF POLYMER ROOF TILES - Nicko Dharma Kustyo; Sunardi Sunardi; Moh. Fawaid; Sidik Susilo; Ipick Setiawan; Yusvardi Yusuf; Agung Sudrajad; Erny Listijorini; Kurnia Nugraha; Slamet Wiyono; Haryadi Haryadi (Trends in Mechanical Engineering Research, 2025)
Roof tiles play a vital role in the construction industry hagoslot by providing protection from the sun's heat and rain. The quality of roof tiles largely depends on the materials used and the manufacturing process, as these factors significantly affect the tiles' mechanical properties. Kangkung pagar (Ipomoea carnea) is one type of alternative natural fiber material that can be utilized in the creation of composite materials. This study aims to explore the potential of Ipomoea carnea powder as an alternative material for producing polymer roof tiles, as well as to examine how variations in the composition of powder and sand influence the mechanical properties of these tiles. The method for producing roof tiles is based on powder metallurgy. The composition of the powder and sand used varies in the following ratios: 10% powder to 50% sand, 20% powder to 40% sand, and 30% powder to 30% sand. Additionally, a fixed composition of 30% polyester resin and 10% asphalt is used. The initial process involves mixing the materials according to these predetermined ratios. The resulting mixture is then molded and compacted under a pressure of 200 kg/cm². Characterization of the mechanical properties includes proximate analysis, calculation of porosity and density, flexural strength testing, and hardness testing.The study's results indicated that the properties of polymer roof tiles are significantly influenced by the composition of the powder and sand used during their manufacture. The findings revealed a porosity value of 0.209%, a density of 0.994%, a flexural strength of 2.270 MPa, and an optimum hardness of 19.1 BHN. The addition of 10% powder increased the hardness value by only 0.4% while decreasing the flexural strength by 0.5%. Overall, the use of Ipomoea Carnea powder was not effective in enhancing the mechanical properties of the polymer roof tiles, as both the flexural strength and hardness values remained below those of commercially available polymer roof tiles.